2004
DOI: 10.1124/mol.104.008417
|View full text |Cite
|
Sign up to set email alerts
|

β-Arrestin-Dependent Spontaneous α1a-Adrenoceptor Endocytosis Causes Intracellular Transportation of α-Blockers via Recycling Compartments

Abstract: The antagonist ligand BODIPY-FL-prazosin (QAPB) fluoresces when bound to bovine ␣ 1a -adrenoceptors (ARs). Data indicate that the receptor-ligand complex is spontaneously internalized by ␤-arrestin-dependent endocytosis. Internalization of the ligand did not occur in ␤-arrestin-deficient cells; was blocked or reversed by another ␣ 1 ligand, phentolamine, indicating it to reflect binding to the orthosteric recognition site; and was prevented by blocking clathrin-mediated endocytosis. The ligand showed rapid, di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
51
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(62 citation statements)
references
References 37 publications
11
51
0
Order By: Relevance
“…The metabotropic glutamate receptor mGluR1a undergoes extensive constitutive agonist-independent internalization that does not involve arrestins, yet its internalization in response to agonist is selectively mediated by arrestin2 (Dale et al, 2001). In contrast, spontaneous internalization of the α1A-adrenoreceptor is arrestin dependent, and this receptor travels with bound arrestin all the way to the recycling endosomes (Pediani et al, 2005). WT serotonin 5-HT4 receptor internalizes via an arrestin-dependent pathway in colliculi neurons naturally expressing it, as well as in COS-7 and HEK293 cells, but the deletion of the main S/T cluster phosphorylated by GRK2 re-directs the receptor to an arrestin-independent pathway and actually increases the rate of its internalization .…”
Section: Does Arrestin Binding Predetermine the Internalization Pathway?mentioning
confidence: 99%
“…The metabotropic glutamate receptor mGluR1a undergoes extensive constitutive agonist-independent internalization that does not involve arrestins, yet its internalization in response to agonist is selectively mediated by arrestin2 (Dale et al, 2001). In contrast, spontaneous internalization of the α1A-adrenoreceptor is arrestin dependent, and this receptor travels with bound arrestin all the way to the recycling endosomes (Pediani et al, 2005). WT serotonin 5-HT4 receptor internalizes via an arrestin-dependent pathway in colliculi neurons naturally expressing it, as well as in COS-7 and HEK293 cells, but the deletion of the main S/T cluster phosphorylated by GRK2 re-directs the receptor to an arrestin-independent pathway and actually increases the rate of its internalization .…”
Section: Does Arrestin Binding Predetermine the Internalization Pathway?mentioning
confidence: 99%
“…Where quantification was to be carried out, a Nikon Diaphot inverted microscope was used equipped with a 40ϫ oil-immersion Fluor objective lens (1.3 NA). A monochromator (Optoscan) was used to excite cells and fluorescence emission was detected by a cooled digital charge-coupled device camera (Cool Snap-HQ; Photometrics, Tucson, AZ), as described previously by others (Pediani et al, 2005). Cells were analysed 24-48 hours after transfection.…”
Section: Microscopymentioning
confidence: 99%
“…In addition to our BODIPY-prazosin data in neonatal cardiac myocytes, recent evidence has shown a large population of α 1 AR's in adult cardiac myocytes [54]. Moreover, expressing α 1a AR's in R-1F cells were predominately found in intracellular organelles [53] and 40% of native α 1 AR's in human smooth muscle cells were intracellular [62]. Prazosin, an αAR antagonist that can act at the sarcolemma and also be transported Functional intracellular receptors have been identified for angiotensin II [63], endothelin-A and -B [64], and β-adrenergic receptors [65] in cardiac myocytes.…”
Section: Discussionmentioning
confidence: 86%
“…BODIPY-prazosin fluoresces when bound to αAR's and remains effectively non-fluorescent when unbound [61]. Images revealed that the majority of data that showed that expressing α 1a AR's in R-1F cells were predominately found in intracellular organelles, including early and late endosomes [53]. These punctate vesicular structures are also apparent in BODIPY-prazosin images from adult mouse cardiac myocytes [54].…”
Section: αAr Localization Determined Using Bodipy-prazosin Is Consistmentioning
confidence: 90%
See 1 more Smart Citation